Aplikasi Android untuk Monitoring Lahan Pertanian secara Realtime Berbasis Internet of Things - Jihot Lumban Gaol; Hindriyanto Purnomo; Budhi Kristianto; Radius Tanone; Yos Richard Beeh; Nina Setiyawati; Markus Permadi; Raynaldo Raynaldo; Riko Yudistira (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
The development of technology is very helpful in agriculture by using the internet to get the information we need. The problem that farmers think of is that they cannot easily and quickly get information in the form of light intensity, precipitation, soil pH, soil moisture, soil temperature, humidity and air temperature. When farmers get the information they need from agricultural land, they usually get information through the internet so they are considered less efficient as it is quite time consuming. To solve this problem, a system is designed using the research and development method (RnD). A new Android-based application that can display data in text and graphics that are more easily accessible to farmers. This study creates an Android-based mobile application based on tests using the Android interface to display information about agricultural land conditions and display graphical data that is updated every 5 minutes. Keywords— Land monitoring, Agriculture, IoT, Android Mobile Application